2018
DOI: 10.1111/apa.14295
|View full text |Cite
|
Sign up to set email alerts
|

Critically ill neonates displayed stable vital parameters and reduced metabolic acidosis during neonatal emergency airborne transport in Sweden

Abstract: During air transport, critically ill neonates displayed stable vital parameters and reduced metabolic acidosis. No transport-related mortality was found, but the high number of extremely preterm infants transported indicates the potential for improving in-utero transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
4
1
1
Order By: Relevance
“…This finding is not unexpected given that these infants are likely to be more ill. Other variables associated with illness severity, such as transports by helicopter and emergent transports, were also associated with increased risk of clinical deterioration. A recent study of neonates in Sweden found no significant change in Ca-TRIPS scores before and after acute airborne transports [17], which contrasts with our findings. This difference may reflect differences in our study population and illness severity, in addition to a larger transport volume.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is not unexpected given that these infants are likely to be more ill. Other variables associated with illness severity, such as transports by helicopter and emergent transports, were also associated with increased risk of clinical deterioration. A recent study of neonates in Sweden found no significant change in Ca-TRIPS scores before and after acute airborne transports [17], which contrasts with our findings. This difference may reflect differences in our study population and illness severity, in addition to a larger transport volume.…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the study by Henry and Trotman (2017) on neonatal transport in Jamaica showed that male patients predominated, the average gestational age was 34.9 weeks and birth weight was 2.3 kg [21]. The research carried out by Frid et al (2018) conducted in Sweden on the basis of the analysis of 187 emergency air transports (acute airborne transports) showed that the average gestational age of the transported babies was 35 weeks (range: 22-42 weeks), and their birth weight was 2627 g (467-5300 g) [22].…”
Section: Discussionmentioning
confidence: 98%
“…The most common reason for transporting patients in incubators by Medical Air Rescue crews in the analyzed material were congenital heart malformations. On the other hand, the study carried out by Frid et al (2018) showed that the main indications for neonatal transport were therapeutic hypothermia after perinatal asphyxia, extremely preterm birth and respiratory failure [22]. Additionally, in Henry and Trotman's study (2017), more than half of all neonatal transports were due to respiratory disorders [21].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Frid et al published different results, showing that extreme prematurity (22%), neonatal asphyxia requiring hypothermia (22%), and respiratory distress (16.0%) were the most common problems for which NETs were performed 22 .…”
Section: Discussionmentioning
confidence: 99%